Minimum Wage and Collective Bargaining Reforms: A Narrative Database for Advance Economies - António Afonso; Jo\~ao Tovar Jalles; Zoe Venter (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper presents and describes a new database of major minimum wage and collective bargaining reforms covering 26 advanced economies over the period 1970-2020. The main advantage of this dataset is the precise identification of the nature and date of major reforms, which is valuable in many empirical applications. Based on the dataset, major changes in minimum wages have been more frequent than in collective bargaining in the last decades, and the majority of these were implemented during the 1980s and 1990s. In our empirical application, we find that minimum wage reforms have a medium-run positive impact on labor productivity and they lead to a fall in the unemployment rate. Collective bargaining reforms do not seem to affect either productivity or capital formation but they have a clear medium-term effect on the labor market. Moreover, collective bargaining reforms are more sensitivity to the prevailing business cycle conditions at the time of the reform (vis-à-vis minimum wage reforms).
Keywords: C22; E24; J31; J52; 330; labour market policies; minimum wage; collective bargaining; labour productivity; growth; local projection